GAMBARAN PENGETAHUAN IBU POSTPARTUM TENTANG POSTPARTUM BLUES DI KLINIK SUNGGAL TAHUN 2017 - Parida Hanum (Universitas Prima Indonesia, 2018)
Postparum blues conditions experienced by nearly 80% of women who have just given birth. This may occur because of unprepared delivery and becoming a mother, too low levels of estrogen, progesterone, prolactin, and esteriol levels, age and parity (young age or the number of persistents experienced may result in postpartum blues), as well as emotional support of husbands and families have a major influence in the contribution of postpartum blues. The purpose of this research is to know the description of Postpartum Mother Knowledge about Postpartum Blues at Sunggal Medan Clinic Year 2017. This method uses descriptive, measuring instrument. The population of this research is all 13 postpartum mothers in Medan singleton clinic. Sampling technique by saturated sampling, data collection using questionnaire. The result of the research is 7 (53,84%) enough knowledge, less 2 (15,28%) people and good 4 (23,07%) people. Knowledge of postpartum mother about postpartum blues Majority of respondents have enough knowledge., It is suggested that mothers increase their knowledge about postpartum blues by seeking lots of information and ask many people who have experienced postpartum as postpartum mother learning process in adapt during postpartum period.